OPTIMALISASI VAKSINASI DALAM RANGKA PENCEGAHAN PENULARAN COVID-19 DI LEMBAGA PEMASYARAKATAN KELAS IIB BANGKO - Ivan Aditya Mileniawan; Mitro Subroto (RIO LAW JURNAL, 2021)
The purpose of writing this article is to provide information and knowledge to readers and personal writers about the covid-19 vaccination program at Bangko Prison in the context of preventing the transmission of the covid-19 virus in prisons. In obtaining data, the authors used field observation techniques and interviews with correctional officers and prisoners and detainees at Bangko Prison. To complete the data, the author also uses a literature study technique by taking information from laws and regulations and reading materials such as: books; scientific journals; and articles. In conclusion, although there are several obstacles that hinder the vaccination program at Bangko Prison, its implementation has been running optimally, it is evident from the number of inmates and detainees who have been vaccinated amounting to 343 people out of a total of 382 people. However, there are only 39 prisoners and detainees who have not been vaccinated.